2020
DOI: 10.33225/jbse/20.19.186
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Comparisons of Students’ Science Success Based on Gender Variability: Evidence From Timss

Abstract: Identifying key determinants of success plays an important role in efforts of assessing the current state of educational practices and implementing effective actions to improve academic performance. Given how important is accurate identification of these determinants for valid comparisons, the aim of this research was to present extensive comparative results on 8th grade students' science success for 39 countries. To this end, a total number of 229,493 students' information obtained from the last cycle of Tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
1
6
1
1
Order By: Relevance
“…In the first and second models, we observed that male and female students differed by approximately 1% according to the MAPE value. In the literature, gender is effective on science success (Aşkın & Öz, 2020;Harker, 2000;Kilic Depren, 2020;Kjaernsli & Lie, 2004;Reilly et al, 2019;Torrecilla Sánchez et al, 2019;Yip et al, 2004). In this study, however, gender was not an effective variable on science success and prediction performance.…”
Section: Research Resultscontrasting
confidence: 58%
See 2 more Smart Citations
“…In the first and second models, we observed that male and female students differed by approximately 1% according to the MAPE value. In the literature, gender is effective on science success (Aşkın & Öz, 2020;Harker, 2000;Kilic Depren, 2020;Kjaernsli & Lie, 2004;Reilly et al, 2019;Torrecilla Sánchez et al, 2019;Yip et al, 2004). In this study, however, gender was not an effective variable on science success and prediction performance.…”
Section: Research Resultscontrasting
confidence: 58%
“…Assessments in international exams help us explore the relationships between student achievement and students themselves, as well as between student achievement and both schools and education systems. By identifying the factors that influence student success, stakeholders can take necessary steps to increase the levels of low achievement in education (Aşkın & Öz, 2020). It is important to determine the functioning or problematic parts of the education system according to scientific data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the results of the scientific attitude effect size test for A group and B group are .52, .54 included in moderate effect and science process skills .53, .56 are included in the moderate effect, fulfilling the requirements for the effectiveness of the PbVLab Model. Active participation of students in virtual laboratory, developing scientific attitude, science process skills through VLab activities Topalsan, (2020); Aşkın & Öz, (2020).…”
Section: Discusionmentioning
confidence: 99%
“…PISA 2018 results again reported that 'girls outperformed boys in science by two score points on average across OECD countries' (OECD, 2019b). Nevertheless, by analyzing the "Trends in International Mathematics and Science Study" (TIMSS) 2015 data, Aşkın and Öz (2020) argued though girls outperformed boys in science in 5 Asian countries, the opposite side was true for Georgia, Italy, Lithuania, and the United States. In a global view, girls have progressed in their science performance, both boys and girls can be successful in learning science.…”
Section: Factors Influencing Students' Science Performance In School Contextmentioning
confidence: 99%